Legal Enforcement Against Violations of Trademark Rights that are in Substantial with the Same Name by Business Actors - Mariam Sati; Onny Medaline; Ida Nadirah (Fox Justi : Jurnal Ilmu Hukum, 2025)
Law enforcement against violations of similar trademark rights by business actors is an important issue in the protection of Intellectual Property Rights in Indonesia. Trademarks function as a special identity for products or services offered by business actors. However, there are still many trademark violations that occur, which are detrimental to registered trademark owners and disrupt healthy business competition. This study aims to identify the forms of trademark infringement that are essentially the same in trademark cases in Indonesia. This study is a descriptive study. Using a normative legal approach method. Conducted by means of literature study. The results of the study show that violations often occur in the form of using names, logos, or displays that resemble registered brands, including invisible brands and three-dimensional brands, which can cause confusion in the community. To overcome this, concrete steps are needed such as improving legal regulations, strengthening the role of law enforcement officers, and providing education to the community and business actors about the importance of brand protection. In addition, the implementation of a digital system in brand registration and supervision can also help improve transparency and efficiency. With a more targeted approach and cooperation between parties, brand rights protection is expected to be stronger, so that it can support healthy business competition and provide legal certainty for brand owners.